(untitled) (World Bulletin of Management and Law, 2022)
Compensation has been an output that employee obtains in the form of pay, wages and also same rewards such as monetary exchange for the duty in order to increase the employee performance. Compensation management has a crucial role in organizations nowadays by which the employee is attracted and motivated. Therefore, this study has proved that compensation management has a direct effect on employee performance. And, the study has been managed by a statistical program SPSS 22.0 and applied in a public sector (North Gas Company) in Kirkuk, Iraq